The Inflammatory Correlates of Hypothalamic-Pituitary-Gonadal Axis Dysfunction in Antiretroviral-Naïve Men with HIV: A Cross-Sectional Analysis of the TNF-α and Testosterone Relationship - Hudari, Harun; Yulianto Kusnadi; Risfandi Ahmad Taskura (HM Publisher, 2025)
Background: In men with untreated Human Immunodeficiency Virus (HIV), the mechanisms underlying testosterone deficiency remain incompletely defined. Chronic inflammation is hypothesized to be a key factor in disrupting the hypothalamic-pituitary-gonadal (HPG) axis. This study aimed to investigate the association between the pro-inflammatory cytokine tumor necrosis factor-alpha (TNF-α) and the HPG axis and to assess this relationship while accounting for nutritional status in ART-naïve men. Methods: We conducted a cross-sectional study of 40 ART-naïve men with HIV in Palembang, Indonesia. We measured serum total testosterone, Luteinizing Hormone (LH), TNF-α, Interleukin-6 (IL-6), and high-sensitivity C-reactive protein (hs-CRP). Hypogonadism was classified as primary (low testosterone, high LH) or secondary (low testosterone, low/normal LH). Spearman’s correlation was used to assess bivariate relationships. A multiple linear regression analysis was performed to determine the independent association of TNF-α and Body Mass Index (BMI) with testosterone levels. Results: All 40 participants (100%) presented with secondary (hypogonadotropic) hypogonadism, characterized by a median total testosterone of 6.48 pg/mL and an inappropriately normal median LH of 3.86 mIU/mL. Serum TNF-α was significantly elevated (median: 10.32 pg/mL). A moderate negative correlation was found between TNF-α and total testosterone (ρ = -0.411, p = 0.008). In the multivariate regression model, both higher TNF-α levels (β = -0.38, p = 0.011) and lower BMI (β = 0.45, p = 0.003) were significant, independent predictors of lower total testosterone. The model explained 34.6% of the variance in testosterone levels (Adjusted R² = 0.346). Conclusion: Our findings demonstrate a universal prevalence of secondary hypogonadism in ART-naïve men with HIV. This HPG axis dysfunction is strongly and independently associated with both the magnitude of systemic inflammation, marked by TNF-α, and the severity of malnutrition. These results suggest a complex interplay where inflammation and poor nutritional status act as distinct, synergistic contributors to the profound endocrine disruption seen in untreated HIV infection.